2000
DOI: 10.1177/03635465000280031001
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Reconstruction of the Medial Patellofemoral Ligament on Patellar Tracking

Abstract: We evaluated patellar tracking in six cadaveric knees with the medial restraints intact and then sectioned to determine their contribution to lateral translation of the patella with and without a lateral force on the patella. The medial patellofemoral ligament was then reconstructed with a gracilis tendon graft and patellar tracking was again evaluated. The knees were extended using a materials testing machine, and patellar tracking was measured with a position sensing system. With no lateral force applied to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
113
0
11

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(129 citation statements)
references
References 11 publications
5
113
0
11
Order By: Relevance
“…3 While most follow-up studies reported that knee flexion after TKA of between 110 to 1208, 4 many studies investigated knee biomechanics in deep flexion to understand the biomechanical factors that may affect flexion capabilities. 1,2,[5][6][7][8][9] Among these factors, the function of the patellar tendon, an essential component of the extensor mechanism, plays a critical role.…”
mentioning
confidence: 99%
“…3 While most follow-up studies reported that knee flexion after TKA of between 110 to 1208, 4 many studies investigated knee biomechanics in deep flexion to understand the biomechanical factors that may affect flexion capabilities. 1,2,[5][6][7][8][9] Among these factors, the function of the patellar tendon, an essential component of the extensor mechanism, plays a critical role.…”
mentioning
confidence: 99%
“…In the last decade, important biomechanical investigations have been carried out confirming the importance of this ligament, demonstrating that it is the most important medial static structure for prevention of the patellar lateral dislocation, contributing with over 50% of this strength (19)(20)21) . An interesting biomechanical essay was performed by Sandmeieret al (22) , in which they promoted the MPFL reconstruction with the tendon of the gracilis muscle, observing reestablishment of normal patellofemoral exam after the ligament reconstruction. An important and little studied aspect of the MPFL is concerned with the maintenance of its function in the different degrees of knee flexion.…”
Section: Discussionmentioning
confidence: 99%
“…[26] In absence of intact MPFL, patellar tracking is significantly affected by a laterally directed force, but returns to normal following reconstruction of MPFL. [27] Patient's selection is very much important while considering for MPFL reconstruction. Before doing MPFL reconstruction, it is important to distinguish common patellofemoral pain syndrome from anterior pain associated with patellar instability.…”
Section: Figure 6 Showing Tt-tg Distance In Overlapped Image Of Mrimentioning
confidence: 99%